Theory of Thematic Curricula - Freeman, Carole Cook; Sokoloff, Harris J. (Education Policy Analysis Archives, 1995)
A theory of thematic curriculum emerged during the development of a unit on pets, entitled Pets & Me. The unit was designed through a school/university partnership for children pre-school to grade 5. Analysis of data collected during the unit's development and field tests supports a dynamic view of curriculum that challenges policy makers to rethink policies that begin from a view of curriculum as a static list of "facts" to be learned or "topics" to be mastered. Reflection on the project led to the differentiation of three distinct constructs: (1) facts and information, (2) topics, and (3) themes. Each of these three constructs plays a different role in children's learning. Facts focus on basic information and narrowly defined ideas understood as discrete items. Topics provide a context for facts and information, and present a way of organizing discrete bits of information into classes of experience recognizable by scholars within traditional disciplines. Themes defined as broad existential questions, transcend disciplines, allowing learners to integrate the information and the topic within the full range of human experience. All three are important elements of thematic curriculum. PREFACE